Caregiver burden and related factors during active cancer treatment: A latent growth curve analysis. (June 2021) - La, In Seo; Johantgen, Meg; Storr, Carla L.; Zhu, Shijun; Cagle, John G.; Ross, Alyson
Abstract : Purpose: Caregiver burden is frequently studied cross-sectionally, but longitudinal studies on family caregiver burden during active cancer treatment are lacking. The goals of this study were to characterize trajectories of caregivers' burden during a 6-month active treatment period, and to examine which predictors are associated with their burden. Method: This study was a secondary analysis of data from a prospective study. A sample of 112 family caregivers of patients receiving cancer treatment were assessed at three time points (the initiation of new treatment regimen, 3-, and 6-month follow-up). Caregivers completed measures: Caregiver Reaction Assessment and Mutuality Scale of the Family Care Inventory. Data were analyzed using latent growth curve modeling. Results: The two highest burdens were subdomains related to disrupted schedule and financial problems. Models showed a decline in schedule burden over time, yet total burden and other subscales (financial problems, health problems, and lack of family support and self-esteem) remained relatively stable. In multivariate analysis, mutuality, the relationship quality between patients and caregivers was inversely related to burden at baseline. Being a spouse, a sole caregiver and lower income were related to higher burden over time. Conclusions: Our findings confirmed significant determinants of caregiver burden over the course of active treatment. It is important for health care providers to be attentive to vulnerable caregivers who are at higher risk of elevated burden over time. Considering the multidimensional nature of caregiver burden, early assessment and tailored support programs may be effective by focusing on patient-caregiver relationships, caregiving roles, and income. Highlights: Latent growth modeling is useful for examining baseline levels and changes of caregiver burden. Patterns over time and factors that influence burden differ, based on each burden dimension. Caregivers who are spouses, sole caregivers, and have lower income were more at risk for higher burden over time.